Peran Belanja Pemerintah Fungsi Pendidikan, Kesehatan, dan Ekonomi terhadap Pembangunan SDM Kalimantan Selatan - Yenie Purnomoratih; Safira Nurdianah Ramadhani (Jurnal Manajemen Perbendaharaan, 2023)
This paper is intended to examines the role of the Government’s consolidated budget for education, health, and economic for the human development in South Kalimantan, and to explore how the budget is implemented. This paper uses panel data regression of consolidated government spending per region for 2017-2021, using the Fixed Effect Model. The result shows that the regional expenditure for education had a significant but counterproductive effect on the formation of HDI. The implementation of the regional budget for education has not been in good quality of spending. Meanwhile the Central expenditure on education had an insignificant effect. This study also found that government expenditure for health, both Central and Regional play a positive and significant role in HDI. Finally, this study shows that central government expenditure in Economics has a significant and positive effect on HDI compared to regional expenditure. In its implementation, there are several regions with poor HDI that do not allocate for Economics.